Continuing professional development for networked learner support: progress review of research and curriculum design - Philippa Levy (Information Research: An International Electronic Journal)
This paper focuses on what has been learnt through the NetLinkS project about professional development and training needs for NLS, and describes the underpinning rationale and curriculum model for the new on-line course. The research on which the paper draws, which aimed to assess the validity of the CPD concepts initially proposed and to feed into further refinement of the curriculum model, was carried out by means of focus group discussions in nineteen UK institutions of higher education during 1995-6, and is currently being followed up by one-to-one interviews with a range of staff with interests and involvement in NLS.